2020
DOI: 10.1002/ajoc.202000575
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Uses of (Me4N)XCF3 (X=S, Se) in the Synthesis of Trifluoromethylthiolated and Trifluoromethylselenolated Compounds

Abstract: The introduction of trifluoromethylthio (SCF 3) and trifluoromethylseleno (SeCF 3) substituents into organic molecules significantly improves the electron-withdrawing and lipophilic properties of their parent compounds. Therefore, a vast class of versatile reagents were employed to access the corresponding fluorine-containing compounds. Among them, tetramethylammonium salts, such as (Me 4 N)SCF 3 and (Me 4 N) SeCF 3 , have been employed as practical and efficient non-metal reagents for developing efficient tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…Compared to trifluoromethylation, trifluoromethoxylation, and trifluoromethylthiolation, the direct trifluoromethylselenylation of alcohols is relatively less explored, although there has been much recent attention on the development of novel and efficient methodologies for the synthesis of SeCF 3 -substituted compounds. 34 In 2019, in the same study describing the deoxytrifluoromethylthiolation of alcohols with the benzothiazolium salt BT-SCF 3 , Hopkinson's research team reported the successful NEt( i Pr) 2 -promoted preparation of trifluoromethylselenoalkanes 36 from the respective alcohols 34 employing 2-trifluoromethylseleno-substituted benzothiazolium salt (BT-SeCF 3 ; 35) ( Scheme 20 ). 31 Notably, BT-SeCF 3 was synthesized via the same general strategy used to prepare BT-SCF 3 .…”
Section: Dehydroxylative Trifluoromethylselenylationmentioning
confidence: 99%
“…Compared to trifluoromethylation, trifluoromethoxylation, and trifluoromethylthiolation, the direct trifluoromethylselenylation of alcohols is relatively less explored, although there has been much recent attention on the development of novel and efficient methodologies for the synthesis of SeCF 3 -substituted compounds. 34 In 2019, in the same study describing the deoxytrifluoromethylthiolation of alcohols with the benzothiazolium salt BT-SCF 3 , Hopkinson's research team reported the successful NEt( i Pr) 2 -promoted preparation of trifluoromethylselenoalkanes 36 from the respective alcohols 34 employing 2-trifluoromethylseleno-substituted benzothiazolium salt (BT-SeCF 3 ; 35) ( Scheme 20 ). 31 Notably, BT-SeCF 3 was synthesized via the same general strategy used to prepare BT-SCF 3 .…”
Section: Dehydroxylative Trifluoromethylselenylationmentioning
confidence: 99%
“…The unique Hansch parameters of CF 3 S and CF 3 Se provide the medicinal chemist with a convenient tool for adjusting the lipophilicity of bioactive molecules, whereas their electron‐withdrawing properties and considerable steric hindrance enhance the metabolic stability of the molecules containing these fluorinated groups. Not surprisingly, synthetic methodologies that introduce SCF 3 and SeCF 3 are being actively pursued [1b,c, 4] . Among them, the direct trifluoromethylthiolation and trifluoromethylselenolation of organohalides with palladium, [5] nickel, [6] and copper [7] have gained the most traction [8] (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…[21,22,36] Conversely, access to alkyl trifluoromethylselenylated entities has proven more challenging, and to date, only a few strategies have been described in the literature. [21][22][23]37] The most expedient way to afford such compounds remains the direct nucleophilic substitution of activated alkyl species with the CF 3 Se À anion to forge the desired C(sp 3 )À SeCF 3 bond (Scheme 1B). [21][22][23]37] Due to the synthetic challenge associated to the generation of the CF 3 Se À anion, several copper-based methodologies have been reported (Scheme 1B, a).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23]37] The most expedient way to afford such compounds remains the direct nucleophilic substitution of activated alkyl species with the CF 3 Se À anion to forge the desired C(sp 3 )À SeCF 3 bond (Scheme 1B). [21][22][23]37] Due to the synthetic challenge associated to the generation of the CF 3 Se À anion, several copper-based methodologies have been reported (Scheme 1B, a). [38][39][40] In 2003, Tyrra and co-workers reported the convenient synthesis of the air-stable (Me 4 N)SeCF 3 reagent [41] which was subsequently used as a trifluoromethyselenylating reagent with various electrophiles by the Zhang group (Scheme 1B, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation